2023
DOI: 10.3390/ijms24065661
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ER Stress with Saikosaponin A to Overcome Resistance under Radiation in Gastric Cancer Cells

Abstract: Saikosaponin A is a triterpene saponin and a potentially bioactive compound derived from Bupleurum falcatum L. However, the molecular mechanisms and effects of saikosaponin A in gastric cancer remain unknown. In the present study, I evaluated the effects of saikosaponin A on cell death and endoplasmic reticulum stress via calcium and reactive oxygen species release. Targeting reactive oxygen species with diphenyleneiodonium and N-acetylcysteine inhibited cell death and protein kinase RNA-like ER kinase signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The dosage of the nanomedicine used for in vivo cancer therapy was based on the consideration of safety, therapeutic effects and previous reports. According to the previously reported literature studies on in vivo cancer therapy, the total dosage of SSA ranged from 5 to 10 mg kg −1 , 37,38 while the dosage of CeO 2 used ranged from 5 to 30 mg kg −1 . 39,40 Herein, the total dosage of SSA (3 × 1.4 mg kg −1 ) and Ce (3 × 5 mg kg −1 ) is significantly lower than the reported maximum dosage.…”
Section: Resultsmentioning
confidence: 99%
“…The dosage of the nanomedicine used for in vivo cancer therapy was based on the consideration of safety, therapeutic effects and previous reports. According to the previously reported literature studies on in vivo cancer therapy, the total dosage of SSA ranged from 5 to 10 mg kg −1 , 37,38 while the dosage of CeO 2 used ranged from 5 to 30 mg kg −1 . 39,40 Herein, the total dosage of SSA (3 × 1.4 mg kg −1 ) and Ce (3 × 5 mg kg −1 ) is significantly lower than the reported maximum dosage.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that radiation combined with the natural product nodakenin overcomes radioresistance by activating ROS, ER stress, and apoptosis in vivo and in vitro in radio-resistant breast cancer models [83]. Radiation combined with the natural product saikosaponin A overcomes radioresistance via the induction of apoptotic cell death in vitro and in vivo in radio-resistant gastric cancer models [84]. The natural flavonoid fisetin combined with radiation also overcomes radioresistance and has a powerful anti-cancer effect in vitro and in vivo in radio-resistant liver cancer models [85].…”
Section: Discussionmentioning
confidence: 99%
“…To account for the build-up effect, 25cm 2 culture asks were entirely lled with culture medium and set in a water phantom. To create the radioresistant cell line 5-8FR, clinically conventional fractionated irradiation was utilized to dispose the 5-8F (2 Gy per fraction, 1 fraction per day, 5 days per week) [23]. The 5-8F proteins at 10 Gy/1 week, 30 Gy/3 week, 50 Gy/5 week, 70 Gy/7 week were obtained during the period.…”
Section: Cell Irradiationmentioning
confidence: 99%